Mapping of pain curricula across health professions programs at the University of Toronto. Issue 1 (1st January 2018) - Murphy, Laura; Lax, Leila; Musa, Renata; Langlois, Sylvia; Kanofsky, Sharona; Hunter, Judith; Kumbhare, Dinesh; Promislow, Sara; Oskarsson, Jon; Davies, Robyn; Cockburn, Lynn; Barry, Maureen; et al.
ABSTRACT: Background: There is a growing societal need for health professional competency in pain care. The University of Toronto Centre for the Study of Pain–Interfaculty Pain Curriculum (UTCSP-IPC) has been offered since 2002. Content and process have been updated annually. In addition, participating health professions programs have advanced their pain teaching. A curricular scan was needed to creatively and constructively advance the UTCSP-IPC. Aim: The aim of this study was to map curricular pain content in participating health professions programs onto the UTCSP-IPC content as a first step to further curriculum design. Methods: UTCSP-IPC committee members and faculty representatives from six health profession programs completed a 27-item online survey in this collaborative action study. Descriptive statistics were completed in Microsoft Excel. Results: The UTCSP-IPC provided an average of 43.3% (range 32%–62%) of total pain content teaching hours to participating health professions students and a range of 8% to 100% of total opioid-related teaching hours. Curricular overlaps and gaps in pain content were identified and will be used to update and inform the iterative design of the UTCSP-IPC. Ninety-three percent of participating health professions faculty indicated that the interprofessional focus on pain care in the UTCSP-IPC was important. Conclusion: This study highlighted the value of the UTCSP and areas of curricular refinement to ensure continued relevance in relationship to pain content within the six participating health professions programs. Mapping a coordinated approach between uniprofessional and interprofessional teaching will both meet the demands of professional competence and create greater applicability to future practice settings.